Control interno y su incidencia en el departamento de avalúos y catastros del gad municipal del cantón Buena Fe, año 2012 - Quintana Mendoza, Eliana Roxanna (2015)
This research entitled "INTERNAL CONTROL AND ITS IMPACT ON THE DEPARTMENT OF APPRAISAL AND FILE THE CITY OF CANTON GAD GOOD FAITH AND YEAR 2012." Buena Fe was performed in the canton in the Department of Cadastre and Valuation of GAD Municipal. According to the results it was concluded that: the internal control made to the Department of Cadastre and Valuation of the municipal GAD Canton Buena Fe results in Confidence Level 62.80% (moderate) and a Risk Level 37.20% (high). The information generated by the activities undertaken during the period 2012 in the Department of Cadastre and Valuation is inadequate and inconsistent level of compliance presented by the Department of Municipal Cadastre and Valuation GAD Good Faith, has been considered as low or deficient, The computer operating system today is art and not reliable and therefore has a system of internal control in the institution. The recommendations made were: Apply all procedures and institutional rules relating to compliance with the public service and resource management such as: Coding Scheme Chapter IV Municipal Municipal and State Government Auditing Standard, Chapter II System National Competency Municipal Coding Scheme. Implement an internal control system in order to improve the functioning of the department of Cadastre and Valuation and to the attainment of directly interrelated goals with corporate goals Find the appropriate mechanisms to institutionalize training processes for officials on planning process, internal control and management processes related to each departmental public affairs area whose purpose is to work together with all departments of the municipal GAD Good Faith.